Eye-hand decoupling decreases visually guided reaching independently of posture but reduces sway while standing: Evidence for supra-postural control. (1st May 2021) - Yeomans, Matthew; Yan, Shijun; Hondzinski, Jan M.; Dalecki, Marc
Highlights: We studied whether coupled and decoupled visually guided reaching differs for sitting and standing. We also examined whether postural control while standing differs between coupled and decoupled reaching. Eye-hand decoupling influenced postural control of stance and goal-directed reaching. Altering posture from sitting to standing only influenced reaching endpoint consistency, independent of cognitive demands. The decoupled task, while standing, may serve as supra-postural task and sway was modulated to support eye-hand control. Abstract: We investigated whether visually guided reaching differs for sitting and standing postures while the eyes and hand are coupled to move in the same direction or decoupled to move in opposite directions. We also investigated how coupled and decoupled reaching tasks influenced standing postural control. Eighteen healthy young adults (M = 21 years) moved a cursor using finger movements along a vertical touchscreen while sitting or standing. In an eye-hand coupling (EH) task, participants moved their finger/cursor from a central target to a peripheral target located either up, down, left, or right. In an eye-hand decoupling (EHD) task, participant's finger movement moved the cursor in the opposite direction. Sway measures during the standing condition and kinematic variables for the cursor offered insight into whole-body control. Performances in EH revealed smaller errors and faster movements than EHD regardless of postural condition. Similar hand movements existed between sitting and standing when accounting for task, while greater variability in absolute endpoint errors existed for standing than sitting when task was ignored. Less postural sway existed for EHD than EH when standing. These data provide evidence that when participants decoupled the eyes and hand movement direction while standing, they attenuated sway to support control of this complex, cognitively demanding, visuomotor task.